2019
DOI: 10.1039/c9md00254e
|View full text |Cite
|
Sign up to set email alerts
|

Design of a MUC1-based tricomponent vaccine adjuvanted with FSL-1 for cancer immunotherapy

Abstract: The designed tricomponent MUC1-based vaccine induced robust immune responses and exhibited a significant reduction in tumor burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…Li and co-workers [158], utilized a 20-mer MUC1 tandem repeat sequence with a Tn antigen in the PDT*RP region conjugated to the fibroblast stimulating lipopeptide 1 (FSL-1, Pam 2 -CGDPKHPKSF) that supports recognition through TLR2 and TLR6 with or without helper T cell epitopes. Immunological results indicate that the tricomponent glycosylated vaccine design stimulated humoral and cellular immune responses that were almost 1.5 times higher than the candidate without the T helper epitope and the antibodies generated from tricomponent vaccine mice bound MCF-7 cancer cells much more effectively.…”
Section: Self-adjuvating Multicomponent Vaccinesmentioning
confidence: 99%
“…Li and co-workers [158], utilized a 20-mer MUC1 tandem repeat sequence with a Tn antigen in the PDT*RP region conjugated to the fibroblast stimulating lipopeptide 1 (FSL-1, Pam 2 -CGDPKHPKSF) that supports recognition through TLR2 and TLR6 with or without helper T cell epitopes. Immunological results indicate that the tricomponent glycosylated vaccine design stimulated humoral and cellular immune responses that were almost 1.5 times higher than the candidate without the T helper epitope and the antibodies generated from tricomponent vaccine mice bound MCF-7 cancer cells much more effectively.…”
Section: Self-adjuvating Multicomponent Vaccinesmentioning
confidence: 99%
“…Likewise, antibody-mediated CDC assay also indicated that the anti-1 sera could mediate strongest killing rate against HER2 overexpressing BT474 breast cancer cells than anti-sera stimulated by vaccine 2 and vaccine 3 under the same conditions, which supported the similar results in previous studies. 20,[23][24][25] Furthermore, tricomponent vaccine 1 with its simple lipopeptide adjuvant-helper T cell epitope P2-minimal epitope conjugated structure also exhibited Th1 and Th2-skewed responses, which strongly supported the self-adjuvanting vaccine strategy with multiple components. In addition, the in vivo results also indicated that immunoadjuvant Pam 3 CSK 4 could stimulated a stronger immune response than the helper T cell epitope.…”
Section: Discussionmentioning
confidence: 98%
“… 24 Zhao et al designed and synthesized a MUC1-based tricomponent vaccine by conjugating MUC1 antigen, a helper T cell epitope P2 (QYIKANSKFIGITE) with lipopeptide FSL-1, and the glycosylated tricomponent vaccine candidate enabled to induce the efficient elicitation of both humoral and cellular immune responses. 25 These studies provided strong evidence to support the design of multicomponent cancer vaccines.…”
Section: Introductionmentioning
confidence: 88%
“…For example, in clinical application, a synthetic MUC1 peptide was used as a vaccine to strengthen the tumor-associated antigen presentation of dendritic cells and to activate cytotoxic T cells in resected and locally advanced pancreatic cancer [ 68 ]. Pancreatic cancer immunotherapy with MUC1-based vaccines reduced the tumor burden by inducing a cellular and humoral response [ 69 ]. The combination of MUC1 antibodies and radioisotopes is an interesting concept, but the side effects of radiotherapy such as neutropenia and thrombocytopenia as well as the high cost should be considered [ 70 , 71 ].…”
Section: Changes Of the Adaptive Metabolic Pathwaysmentioning
confidence: 99%